Chance-constrained supply function equilibrium model of electricity markets with wind generation - Pacaba, Dominic Dave P. (College of Engineering, University of the Philippines Diliman color illustrations, 2014)
The demand for wind generation is increasing around the world. However, the increase in wind generation in an electric power system also increases the uncertainty in supply and can affect how Generating Companies (GenCos) strategize in the electricity market thereby also affecting electricity prices. The study introduces a method for simulating the effects of different wind generation conditions on the electricity market, particularly the effects on GenCo market strategy and on electricity market prices. A supply function equilibrium model is formulated for the electricity market, with a chance constraint added to accommodate the introduction of wind generation resources. The chance constraint used indicates the probability of the demand being satisfied by the supply, which translates to the probability of the amount of generation from wind resources. The study used the IEEE 30-bus test system, which consists of six generating units, to determine the effects of different system confidence levels, wind penetration levels, wind probability parameters, and wind turbine parameters. The results indicate that changes in the parameters used in the model affects the allowable wind generation for each market clearing. Although the increase in wind generation decreases the electricity market price, prices do not decrease proportionally with respect to increasing generation due to the changes in the strategies of GenCos. The model can be useful for planning electricity markets with integration to determine the best strategies of GenCos and how the addition of the wind resources affects the market prices.